Fatigue-induced hip-abductor weakness and changes in biomechanical risk factors for running-related injuries - Radzak, K.; Stickley, C. D. (Journal of Athletic Training, 2020)
Context: Despite overlap between hip-abductor (HABD) weakness and fatigue-induced changes in running, the interaction of these theorized contributors to running injuries has been underevaluated. Objective: To assess the effects of a fatiguing run on HABD torque and evaluate the correlation between HABD torque and previously identified running-related injury pathomechanics while participants were rested or fatigued. Design: Crossover study. Setting: Laboratory. Patients or Other Participants: A total of 38 healthy, physically active males (age = 21.61 ± 4.02 years, height = 1.78 ± 0.08 m, body mass = 76.00 ± 12.39 kg). Intervention(s): Data collection consisted of rested-state collection, a fatiguing treadmill-run protocol, and fatigued-state collection. For the HABD measures, side-lying handheld-dynamometer isometric tests were performed and converted to torque using femur length. For the gait analysis, kinematic (240 Hz) and kinetic (960 Hz) running (4.0 m/s) data were collected for 3 trials. The fatigue protocol involved a graded exercise test and 80% o2max run to exhaustion. Immediately after the run, fatigued-state measures were obtained. Main Outcome Measure(s): Variables of interest were HABD torque and peak angles, velocities, and moments for hip and knee adduction and internal rotation. Differences between conditions were compared using paired t tests. Pearson correlation coefficients were calculated to evaluate relationships between HABD torque and biomechanical variables. Results: Fatigue decreased HABD torque and increased hip-adduction angle, knee-adduction velocity, and hip and knee internal-rotation velocities and moments (all P values < .05). In the rested state, HABD torque was correlated with hip-adduction velocity (r = -0.322, P = .049). In the fatigued state, HABD torque was correlated with hip-adduction velocity (r = -0.393, P = .015), hip internal-rotation velocity (r = -0.410, P = .01), and knee-adduction angle (r = 0.385, P = .017) and velocity (r = -0.378, P = .019). Conclusions: Changes in joint velocities due to fatigue and correlations between HABD torque and hip- and knee-joint velocities highlight the need to consider not only the quantity of HABD strength but also the rate of eccentric control of HABDs.